Determination of Forage Crops Producer Behavior In Agriculture In Harran Plain - Gülşah BENGİSU and Büşra ÇEKİLMEZ (ISPEC Journal of Agricultural Sciences, 2020)
This investigation; in order to determine the approach of the producers in the villages of Altı, Belitaş, Bulgurlu, Balkat, Aşağı Close Road, Su Geldi and Agriculture District Directorate in Harran district of Şanlıurfa province to the production of forage plants and their thoughts on the "Feed Plant Production Development Project" implemented in 2018. has been made. Survey questions were prepared for this purpose, a total of 60 producers in 6 villages selected by chance and Harran Tarım district directorate were interviewed face to face, the survey results were prepared, the results obtained were evaluated and interpreted. According to the producers as a result of the research, among the reasons why the forage crop farming is not developed; Inadequate policies applied to forage crops, insufficient implementation of incentives and supports, high input costs and low yield can be listed.